PENINGKATAN PENDAPATAN KELOMPOK TANI PADI ORGANIK MELALUI PROGRAM MANDIRI BENIH DI DESA KETAPANG KECAMATAN SUSUKAN SEMARANG - Supriyadi Supriyadi; Sumani Sumani; Purwanto Purwanto; Mustofa Mustofa (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2017)
Background, excessive exploitation of paddy land in the long term without the addition of organic matter have resulted in soil become damaged. To meet the needs of food (rice) healthy and improve the functioning of the land, then there is no best alternative except development of organic farming systems. To be able to implement a system of organic farming, it is necessary to aplication of seed quality assurance. IbPUD activities carried out ini the village Ketapang, local village government has formed group of paddy organic farmers, but due to constraints in the available of seed rice organic . The purpose, carry out assistance to Farmers and Farmers Group in the establishment of the sources of seed organic rice and the acquisition of organic certification. The method, is Focus Group Discussion which emphasizes dialogue interpersosnal and mentoring. The program is implementing educational methods that involve the active participation of the participants from the three (3) groups of paddy organic farmers partners in Ketapang. The training was held in the form of : (1) seed rice breading management trainin, (2) training of organic rice management with the use of local waste and can be as alternative of organic fertilizers, and (3) training buines management.Results, an increasing number of farmers' groups who implement sources of seed organic rice of 4 (four) varietas (Mentik Susu, Mentik Wangi, Hitam Arang and Merah Anoman) to 3 farmer groups (15Ha). In conclusion, most members of the Farmers Group Al-Barokah have felt: (a) the benefit of the treatment of organic in terms of soil quality and the products of organic rice and its by-products, (b) an increase in value-added organic products and farmers' income, (c) the importance of maintaining paddy according to its function, (d) have become independent farmers in organic rice cultivation.Keywords: Organic farming systems, Organic certification, Interpersonal dialogue